Pembelajaran Inkuiri Berbasis Demonstrasi Pada Materi Energi untuk Menanamkan Sikap Ilmiah Siswa Sekolah Dasar - Rafa Fatin Fauziyah; Anatri Desstya (Universitas Negeri Padang, 2024)
Science education in fourth-grade elementary school is still inclined towards a teacher-centred approach, where students prioritize memorizing theories and concepts. This results in a lack of development in scientific attitudes and students' absorption of the material. This research aims to describe the cultivation of scientific attitudes through the inquiry-based demonstration learning method. The research methodology is qualitative, utilizing data collection through observation, interviews, and documentation at SD Negeri Kedungwaduk 1 in Sragen. The study involves teachers and fourth-grade students as research subjects. The research findings indicate that the cultivation of scientific attitudes using the inquiry-based demonstration method reached 73.46%. Successfully instilled scientific attitudes include: 1) Curiosity at 64%, 2) Response to data/facts at 100%, 3) Critical thinking at 35%, 4) Discovery and creativity at 57%, 5) Open-mindedness and cooperation at 100%, 6) Independence at 71%, and 7) Environmental awareness at 85%. However, further intervention is needed to enhance critical thinking, which is currently at 35%, through exploration, experimentation, discovery, and small-group learning.